2020
DOI: 10.1038/s41598-020-69915-x
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal volatile fatty acid absorption is affected by elevated ambient temperature

Abstract: The objective of this study was to investigate the effect of short-term elevated ambient temperature on ruminal volatile fatty acid (VfA) dynamics and rumen epithelium gene expression associated with the transport and metabolism of VFA. Eight ruminally cannulated Holstein heifers (200 kg) were used in a factorial, repeated measures experiment with two treatments and two periods. During the first period, animals were provided with feed ad libitum and housed at 20 °C. During the second period, one group (HS) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
4
21
0
1
Order By: Relevance
“…Earlier studies also reported a significant decrease in VFA production during heat stress conditions [ 59 , 60 , 61 ]. In contrast, butyrate absorption through the rumen epithelium could greatly decrease under heat stress [ 62 ], which corroborates the significantly higher butyrate concentration observed in the present study during high THI in summer. Both seasons and breeds also had a significant influence on the A:P ratio.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies also reported a significant decrease in VFA production during heat stress conditions [ 59 , 60 , 61 ]. In contrast, butyrate absorption through the rumen epithelium could greatly decrease under heat stress [ 62 ], which corroborates the significantly higher butyrate concentration observed in the present study during high THI in summer. Both seasons and breeds also had a significant influence on the A:P ratio.…”
Section: Discussionsupporting
confidence: 91%
“…Increased VFA levels are also related to feed intake via the control of satiety and hunger, as it has been reported that elevated propionate levels reduce eating behaviour by affecting satiety through brain striatal pathways (Bedford et al, 2020;Byrne et al, 2016). Therefore, in the present study, the decreased feed intake may have been affected by the elevated caecal propionate level; infusion of propionate altered the feeding behaviour and decreased energy intake, supporting this prediction (Oba and Allen, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…However, in the result of correlations of identified metabolites in pigs, there was a negative correlation between the concentrations of acetate and propionate. This result might be due to the conversion of propionate to acetate by decreased feed intake under HS condition was stronger than that of acetate to propionate [45].…”
Section: A C C E T E Dmentioning
confidence: 92%
“…Because it was previously reported that infusion of propionate decreased feed intake by affecting satiety [46]. There was also a result of interconversion between acetate and propionate by the HS [45]. However, in the result of correlations of identified metabolites in pigs, there was a negative correlation between the concentrations of acetate and propionate.…”
Section: A C C E T E Dmentioning
confidence: 97%
See 1 more Smart Citation